Literature Review of Biolarvacide Testing from Gadung Tuber (Dioscorea hispida) for Aedes aegypti Mosquito Larvae - Risma Mawardah (Universitas Veteran Bangun Nusantara, 2021)
Efforts to prevent the dengue virus, which is transmitted by the Aedes aegypti mosquito with vegetable larvicides, have not been maximally utilized. Gadung tuber (Dioscorea hispida) is a type of plant that has high potential as vegetable larvicides because it contains HCN toxins. This literature review aims to determine the concentration of gadung tuber extract which is effective for larvicide against the mortality of Aedes aegypti mosquito larvae. The independent variable in this literature review is the concentration of gadung tubers (Dioscorea hispida) and the dependent variable is the mortality of Aedes aegypti mosquito larvae. The article was obtained from Google Scholar, using the keyword